Marketing strategies for the relaunch of the professional career of economic engineering in the socioeconomic context - PUYÉN FARÍAS, Nelson Alejandro (2020)
In the last calls for admission, applicants were interested in the career of Economic Engineering, but since 2016, it was no longer considered as an alternative at Señor de Sipán University. The objective of this research is to develop marketing strategies for the relaunch of the economic engineering professional career in the socio-economic context of 2019 in order to achieve a sustainable professional school, which provides a quality educational service and complies with meet local, regional and national demand. The Theory of consumer choice was worked on; marketing strategies such as relationship marketing, and marketing mix. The type of research used was explanatory and purposeful with a non-experimental cross-sectional design. The sample was established with 1,157 students in the 5th year of secondary education from the main private and national educational centers of the departments of Lambayeque, Cajamarca, San Martín and Amazonas. From the results of the surveys, an unsatisfied demand of a range of 82 to 148 students per year was evidenced, who prefer to study at the Señor de Sipán University, this is because the study programs are differentiated by the spatial approach and sustainability that offers the curriculum, the quality of the infrastructure, the academic resources, the relevance of the functional map, the teaching-learning processes and the recognized teaching staff.Keywords: Marketing strategies, Economic Engineering, socioeconomic context.